If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x+3)=2x-7
We move all terms to the left:
5(x+3)-(2x-7)=0
We multiply parentheses
5x-(2x-7)+15=0
We get rid of parentheses
5x-2x+7+15=0
We add all the numbers together, and all the variables
3x+22=0
We move all terms containing x to the left, all other terms to the right
3x=-22
x=-22/3
x=-7+1/3
| -12=4y+8 | | 1/3d+15=-30 | | 6x+2=9x10 | | -8v+3(v-2)=34 | | 1.1m+0.02=1.45-4.81m | | 5(z-1)=2(z-4)-6 | | -2x-13=-49 | | -3(x+11)=21 | | -4=4(w+2)-6w | | 3x+5=17x-19 | | (10−3x−1)/2=)6x+3)/11 | | 45=0.50+0.05m | | -5-5x=1-6x | | -w+162=104 | | -1+6n=-19 | | )10−3x−1)/2=)6x+3)/11 | | –8−b=b | | 16-v=162 | | y-8+5=7 | | j=(2j+-3) | | 5k+9=10(1/2*k+1) | | -10x=-19 | | 9a=10a^2 | | 2-5/3u=7/3-8/9u | | -5x-14=-3 | | 7=k/3+4 | | 2a=0.8 | | -10y=110 | | 0.25x+2x=2x-1.75 | | 70+x+x-20=18 | | 1(0−3x−1) /2=(6x+3 )11 | | (x2+6=5x |